From Isolation to Momentum: Understanding Natuna’s Village Development Through Circular Causation - Yogi Pasca Pratama; Dinarjati Eka Puspitasari; Hurng-Jyuhn Wang; Anang Pra Yogi; Salju Indara Zeith Geisth; Hastin Nariswari (Commodities, Journal of Economic and Business, 2025)
Strategic borderlands and regional development In strategic border regions,?we find a complex politico-geographical dynamic between the imperatives of state territorial security on one hand, and economic under-development on the other. It’s about Natuna?Regency, Indonesia's "front-door" in the North Natuna Sea, which is emblematic of the unique paradox of high resource potential and long-standing development lags. The research examine 77 village units in Natuna to investigate regional development trajectories through Gunnar Myrdal’s perspective of Circular and Cumulative Causation (CCC), exploring the mechanisms of economic “locking” mechanisms of borderland economy. The methodology employs an advanced?k-prototype clustering algorithm to interpret high-dimensional Podes 2025 secondary data. This model uses mixed-type variables (i.e., digital, infrastructure or the presence of BTS and signal strength), economic facilities (credit access/KUR) as well as environmental?risk factor to analyze spatial-economic disparities. The analysis reveals three clusters-Growth Poles (Bunguran Timur), with a?"virtuous cycle" of digital-institutional synergy, The Agricultural Periphery in the form of a "backwash effect," associated with logistical bottlenecks, and Isolated Maritime Units facing cumulative decay. The study reveals that borderland resilience cannot be solely attributed to physical infrastructure but to the management of the compounded effect of innovation. The present research provides a strategic blueprint for sub-national governance to harness secondary data for policy-making in critical maritime areas.